Correlation between Carbohydrate Consumption Level, Physical Activity and Quality of Sleep with Current Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus at PUSKESMAS Rapak Mahang Tenggarong - Rossa Dwiana Putri; Kurniati Dwi Utami; Sepsina Reski (PT FORMOSA CENDEKIA GLOBAL, 2022)
The 2018 Riskesdas report states that the prevalence of DM based on the results of blood glucose levels in the province of East Kalimantan, especially in Kutai Kartanegara Regency, is 69.4%. This shows that DM cases in East Kalimantan, especially the Tenggarong area, Kutai Kartanegara Regency, are still a problem. This study aims to determine the relationship between the level of carbohydrate consumption, physical activity and sleep quality with blood glucose levels during type 2 diabetes mellitus at Rapak Mahang Tenggarong Health Center. This research used a cross sectional study design. The results showed that there was a relationship between the level of carbohydrate consumption and blood glucose with a p value = 0.023 (p <0.05). There is no relationship between physical activity and blood glucose with p value = 1.000 (p > 0.05). There is no relationship between sleep quality and blood glucose with p value = 0.957 (p > 0.05).